(untitled) (Spectrum Journal of Innovation, Reforms and Development, 2025)
The article deals with the topical issues of the functioning of the psychological service in modern conditions. Psychological assistance is becoming an integral part of the social infrastructure, every year becoming more and more important. In the conditions of a dynamically developing society, the increase in the need for psychological support has become an important part of social work. psychological service, as well as the challenges and problems faced by specialists in this field. Various models of psychological service are investigated, the problems of ethics in the work of psychologists and approaches to the training of specialists are analyzed.